Specific Jak3 Downregulation in Lymphocytes Impairs γc Cytokine Signal Transduction and Alleviates Antigen-driven Inflammation In Vivo - Alicia G Gómez-Valadés; María Llamas; Sílvia Blanch; José C Perales; Juan Román; Lluís Gómez-Casajús; Cristina Mascaró (Elsevier, 2012)
Jak3, one of the four members comprising the Jak family of cytosolic tyrosine kinases, has emerged as a promising target for nontoxic immunotherapies. Although a number of Jak inhibitors has already demonstrated efficacy, they suffer from secondary effects apparently associated to their pan-Jak activity. However, whether selective Jak3 inhibition would afford therapeutic efficacy remains unclear. To address this question we have investigated the immunosuppressive potential of selective Jak3 intervention in lymphocytes using RNA interference (RNAi) technology in vitro and in vivo. Using synthetic small interference RNA (siRNA) sequences we achieved successful transfections into human and mouse primary T lymphocytes. We found that Jak3 knockdown was sufficient to impair not only interleukin-2 (IL-2) and T cell receptor (TCR)-mediated cell activation in vitro, but also antigen-triggereds welling, inflammatory cell infiltration, and proinflammatory cytokine raise in vivo. Furthermore, Jak1 (which mediates γc cytokine signaling in conjunction with Jak3) cosilencing did not provide higher potency to the aforementioned immunosuppressant effects. Our data provides direct evidences indicating that Jak3 protein plays an important role in γc cytokine and antigen-mediated T cell activation and modulates Th1-mediated inflammatory disorders, all in all highlighting its potential as a target in immunosuppressive therapies.